2018
DOI: 10.1111/jcmm.13469
|View full text |Cite
|
Sign up to set email alerts
|

miR‐15b‐5p facilitates the tumorigenicity by targeting RECK and predicts tumour recurrence in prostate cancer

Abstract: MicroRNAs (miRNAs) have been reported to participate in many biological behaviours of multiple malignancies. Recent studies have shown that miR‐15b‐5p (miR‐15b) exhibits dual roles by accelerating or blocking tumour progression. However, the molecular mechanisms by which miR‐15b contributes to prostate cancer (PCa) are still elusive. Here, miR‐15b expression was found significantly up‐regulated in PCa in comparison with the normal samples and was positively correlated with age and Gleason score in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 36 publications
(61 reference statements)
2
39
1
1
Order By: Relevance
“…Consistent with these findings, the present study demonstrated that GPR120 plays a critical role in the development of OA. Studies show that miR‐15b‐5p exhibits dual roles by accelerating or blocking tumor progression . Importantly, a recent study shows that miR‐15b is a key regulator of proliferation and apoptosis of chondrocytes from patients with condylar hyperplasia by targeting insulin‐like growth factor 1 (IGF1), IGF1 receptor (IGF1R) and B‐cell CLL/lymphoma 2 (BCL2) …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, the present study demonstrated that GPR120 plays a critical role in the development of OA. Studies show that miR‐15b‐5p exhibits dual roles by accelerating or blocking tumor progression . Importantly, a recent study shows that miR‐15b is a key regulator of proliferation and apoptosis of chondrocytes from patients with condylar hyperplasia by targeting insulin‐like growth factor 1 (IGF1), IGF1 receptor (IGF1R) and B‐cell CLL/lymphoma 2 (BCL2) …”
Section: Discussionmentioning
confidence: 99%
“…The other reasonable explanation is that caspase 3 could be positively affected by certain genes which are targeted by miR-15b. Indeed, enhanced expression of miR-15b in a prostate cancer cell line inhibited reversion-inducing cysteine-rich protein with Kazal motifs (RECK) signal activation, thereby leading to caspase 3 reduction 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Investigating along these lines, MAGI2-AS3 has been experimentally demonstrated to regulate the expression of three miRNAs-miR-15b-5p, miR-374a-5p, and miR-374b-5p that were previously associated with this lncRNA in other cancers [31][32][33]. It is indeed interesting to note that these three miRNAs that are upregulated in EOC [36] have been reported to have oncogenic roles in several other cancers [38,40,41,[49][50][51][52][53][54][55][56][57][58]. It should be mentioned that some miRNAs, for example miR-15b-5p, have been observed to have conflicting roles as both oncogenes and tumor suppressors [49,50,59].…”
Section: Discussionmentioning
confidence: 97%
“…miRNAs check the expression of specific proteins by complementary binding to their mRNA transcripts and cause their degradation [17]. Therefore, to further expand the ceRNA network of MAGI2-AS3, four mRNAs-HOXA5, MTSS1, PTEN, and RECK, reported to be associated with at least one of these three miRNAs-miR-15b-5p, miR-374a-5p, and miR-374b-5p (shown in Supplementary Materials Table S4) [37][38][39][40][41] and having oncosuppressive functions in OC [42][43][44][45] were selected. To determine their involvement in MAGI2-AS3 ceRNA network, the co-expression pattern of MAGI2-AS3 with each of the four mRNAs (HOXA5, MTSS1, PTEN, and RECK) in both OC (TCGA-OV) and FT (GTEx) was examined, as shown in Supplementary Materials Figure S2.…”
Section: Expression Of the Tumor Suppressor Mrnas Abrogated By Mirna mentioning
confidence: 99%